Echoes of the crises in Spain and US in the Colombian labor market: A differences-in-differences approach - Luis E. Arango; Dolores de la Mata; Nataly Obando (SERIEs - Journal of the Spanish Economic Association, 2015)
This paper presents evidence of the effect of the recent phases of the business cycle in Spain and United States, proxied by their respective unemployment rates, on the labor market of Colombian cities with high migration tradition. These countries are the main destination for Colombian labor migrants. By using information from the household survey between 2006 and 2011 for urban areas in Colombia and a differences-in-differences approach, we find that unemployment rates of those countries negatively affect the probability of receiving remittances and the amount received by Colombian households living in areas with high and moderate migration tradition. In a second stage, we provide evidence that unemployment rates of those countries positively affect labor force participation decisions in Colombian regions with the highest migration tradition.
Keywords: C21; J21; J22; 330; Migration; Remittances; Labor participation; Spanish and United States unemployment rates